Accurate Optical Modeling of Monolithic Perovskite/Silicon Tandem Solar Cells and Modules on Textured Silicon Substrates - Lujia Xu; Jiang Liu; Keith McIntosh; Malcolm Abbott; Erkan Aydin; Thomas Allen; Michele De Bastiani; Maxime Babics; Jingxuan Kang; Mohammed Alamer; Wenbo Yan; Wenzhu Liu; et al. (PRX Energy, 2022)
Light-ray tracing (RT) and the transfer matrix method (TMM) allow detailed optical simulation of single-junction silicon and perovskite solar cells, which critically aids device design towards record performance. However, their accuracy is compromised when simulating monolithic perovskite/silicon tandem devices built from textured silicon substrates, due to the resulting complex top-cell morphologies. The associated front surfaces of such tandem devices are typically either roughly conformal to the textured silicon underneath (for thermally evaporated or hybrid-deposited perovskites) or flattened (for solution-processed perovskites). Here, we develop accurate optical models for each configuration. For the conformal-like morphology, we apply a texture-on-texture model to accommodate for local imperfect conformalities. Contrastingly, for the flattened morphology, we develop a multi-subcell model to solve the limitation that films must be conformal in one-step RT + TMM simulations. We verify our models with experimental light absorption and quantum efficiency data for photovoltaic cells and modules in both morphological configurations and identify primary sources of parasitic light absorption. Finally, we extend our simulations to module-scale optics and find that textured module glass can effectively suppress photon escape for both tandem-device morphologies, improving their module performance.